2021
DOI: 10.3390/molecules27010193
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Molecular Fluorescent Conversion from Aggregation-Caused Quenching to Aggregation-Induced Emission by Positional Isomerization

Abstract: In this work, we synthesized a pair of positional isomers by attaching a small electron-donating pyrrolidinyl group at ortho- and para-positions of a conjugated core. These isomers exhibited totally different fluorescent properties. PDB2 exhibited obvious aggregation-induced emission properties. In contrast, PDB4 showed the traditional aggregation-caused quenching effect. Their different fluorescent properties were investigated by absorption spectroscopy, fluorescence spectroscopy, density functional theory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Further application of 4F , especially exploring its use in security inks under acidic conditions, 52 has been demonstrated, as shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…Further application of 4F , especially exploring its use in security inks under acidic conditions, 52 has been demonstrated, as shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…Small nanoparticles were clearly observed with TEM, which is indicative of the self-assembly of TPE-Py molecules. The nanoparticles showed weak emission probably due to the ICT effect [ 48 , 49 , 50 ]. The DLS analysis further indicated that the nanoparticles were dispersed and possessed high positive charges (zeta potential = 5.7), which could be ascribed to the quaternary ammonium salt groups on their surface.…”
Section: Resultsmentioning
confidence: 99%
“…[145][146][147][148] During the detection of plaques, traditional fluorescence nanoprobes often exhibit limited photostability, a narrow stokes shift, and an aggregationcaused quenching effect. [149][150][151][152] In contrast, the recently developed aggregation-induced emission luminogens (AIEgens) have demonstrated potential in addressing the limitations of conventional nanoparticles for fluorescence imaging. [153][154][155] Importantly, AIEgens can be functionalized with targeted ligands to enable precise detection of atherosclerotic plaques.…”
Section: Fluorescence (Fl) Imagingmentioning
confidence: 99%